Financial Statement Analysis For Cryptocurrency In Public Companies - Ayu Kurnia Sari; Hendra Saputra; Saidatunur Fauzi Saidin; Ginta Puspita (International Journal of Management, Economic and Accounting, 2025)
The rapid development of cryptocurrency has not only impacted the digital financial market but also the financial reporting of public companies involved in crypto asset transactions and investments. This study aims to analyze how cryptocurrency is recognized, measured, and presented in the financial statements of public companies, as well as its impact on financial performance and information transparency for investors. The research method used a descriptive qualitative approach, using literature studies and analysis of the financial statements of several international public companies that have adopted cryptocurrency in their business activities. The results show that cryptocurrency recording still faces challenges related to varying accounting standards in each country, particularly in determining fair value, asset classification, and recognizing gains and losses. The analysis also found that cryptocurrency adoption can increase potential profitability, but at the same time increases the risk of asset value volatility. Therefore, public companies integrating cryptocurrency need to implement robust internal control systems, ensure reporting transparency, and keep abreast of developments in international accounting regulations to provide relevant and reliable information to stakeholders.